Identifying and Serving English Learners in Gifted Education: Looking Back and Moving Forward. (December 2020) - Mun, Rachel U.; Hemmler, Vonna; Langley, Susan Dulong; Ware, Sharon; Gubbins, E. Jean; Callahan, Carolyn M.; McCoach, D. Betsy; Siegle, Del
Although the number of English learners (ELs) in the United States continues to increase, this population remains underserved by gifted and talented (GT) education programs across the nation. This underrepresentation represents a societal and research dilemma for reasons we address in this systematic review of the most effective practices documented to identify and serve ELs for GT programs. We examine 50 theoretical and empirical articles according to four major themes: nomination, screening/assessment, services, and identification models. We discuss identification recommendations, including outreach and professional learning to foster stakeholder recognition of GT potential in all ELs, an equitable referral process based on a multiple-lens approach, and observation of students completing problem-solving tasks. Finally, we address perceived best practices in serving GT ELs, including making accommodations for ELs in GT programs.